Discrepancies and Similarities Between Online and Face-to-Face Teachers’ Use of Open Educational Resources (OER) for Teaching Purposes - Dashtestani, Reza; Suhrawardi, Ahmad Mohamadi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
The integration of open educational resources (OER) in the educational curricula of universities and educational organizations has gained tremendous popularity. However, there is a gap in research on teachers’ attitudes toward OER in many developing countries. Using a mixed-methods approach, this study explored the use of OER by online and face-to-face teachers of English as a foreign language (EFL) in Iran. A total of 62 teachers (31 online teachers and 31 face-to-face teachers) participated in the study. Survey and interview results indicated that there were significant differences between online and face-to-face teachers’ attitudes toward OER. Online teachers had a more positive attitude toward OER than face-to-face teachers. The perceived benefits of OER included developing the flexibility of curricula, encouraging personalized learning, and offering pedagogical options for teachers. There were several perceived OER-based challenges in the educational context of Iran as well. The challenges included teachers’ uncertainty about copyright issues, the low quality of OER, teachers’ low levels of digital literacy, teachers’ unawareness of the existence of OER, the lack of quality control over OER, the lack of credibility of OER content, and the lack of up-to-dateness of OER. There were also significant differences between participants’ perspectives on the types and frequency of using OER. More specifically, online teachers used OER for teaching practices more frequently than face-to-face teachers. Participants perceived that they needed various types of training for the appropriate use of OER. This study proposes several implications for renewing and improving teacher training/education programs and material development projects.